2022
DOI: 10.3390/met12071121
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study into the Effect of Machining on the Interaction between Surface Roughness and Surface Breaking Defects on the Durability of WAAM Ti-6Al-4V Parts

Abstract: The airworthiness certification of military aircraft requires a durability analysis be performed using linear elastic fracture mechanics (LEFM). Furthermore, such analyses need to use a valid small crack growth equation. This paper focuses on the effect of rough surfaces and the effect of machining the surface on the durability of AM parts using LEFM and a valid small crack growth equation for the material. To this end, this paper analyses the effect of surface roughness on wire and arc additively manufactured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Practitioners in the field of additively manufactured structures have long been aware [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] that the interaction of surface-roughness with surface-breaking material discontinuities and surface-breaking porosity/lack of fusion can significantly degrade the durability and damage tolerance (DADT) of an additively manufactured part. Indeed, ref.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Practitioners in the field of additively manufactured structures have long been aware [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] that the interaction of surface-roughness with surface-breaking material discontinuities and surface-breaking porosity/lack of fusion can significantly degrade the durability and damage tolerance (DADT) of an additively manufactured part. Indeed, ref.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this observation is consistent with the seminal finding reported by Schijve [20], and subsequently confirmed in [21][22][23][24], that for conventionally built parts internal cracks grow much slower than the surface-breaking cracks. Whereas [17][18][19] suggested that machining the rough surfaces may improve the DADT of an AM part, the studies presented in [2,15] suggested that partial machining may be of little benefit. However, the analysis presented in [2] examined an idealized (rough) surface where the surface roughness had a wave-like (sinusoidal) pattern.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations